Low-Dose Perioperative Corticosteroids Can Be Administered Without Additional Morbidity in Patients Undergoing Bilateral Total Knee Replacement: A Retrospective Follow-up Study of a Randomized Controlled Trial. Issue 1 (February 2022) - McLawhorn, Alexander S.; Poultsides, Lazaros A.; Sakellariou, Vasileios I.; Kunze, Kyle N.; Fields, Kara G.; Jules-Elysée, Kethy; Sculco, Thomas P.
Background: Short-term benefits of perioperative corticosteroid injections (CSIs) for bilateral total knee replacement (BTKR) include suppressed inflammation, improved knee motion, and reduced pain. Very little is known about the long-term benefits, complications, and safety of corticosteroids administered in the perioperative period. Purpose : We sought to compare 3-year follow-up outcomes of BTKR patients who received perioperative CSI with those who received placebo. We hypothesized that there would be no statistically significant differences in functional outcomes or adverse events based on whether or not CSIs were administered in the perioperative period. Methods : We conducted a retrospective review of chart and registry data of BTKR patients from a prior randomized controlled trial to compare outcomes in patients who received hydrocortisone vs placebo injections after BTKR (ClinicalTrials.gov: NCT01399268 and NCT01815918). Outcomes were compared at 6 and 12 weeks and at 1, 2, and 3 years. The Knee Injury and Osteoarthritis Outcome Scores (KOOS) and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) were used to evaluate clinical outcomes. Cochran-Mantel-Haenszel tests were used to compare the risk of complications between treatments after adjustment for trial. When possible, summary relative risk estimates were calculated using the Mantel-Haenszel method. Results : No BTKR patients in the treatment group developed an infection. The risk of complications did not increase in patients who received CSI compared with those who received placebo. Patients in the CSI group experienced greater reductions in pain and stiffness, though these results were not statistically significant. There were no statistically significant differences in the KOOS-Symptoms, KOOS-Activities of Daily Living, KOOS-Sports, KOOS-Quality of Life, or WOMAC Function scores. Conclusions : Low-dose corticosteroids can be administered in selected patients who undergo BTKR without increasing the risk of adverse events. At 3-year follow-up, administration of low-dose corticosteroids did not result in superior clinical outcomes scores when compared with placebo.